2021
DOI: 10.1186/s13287-021-02140-z
|View full text |Cite
|
Sign up to set email alerts
|

Biological characteristics of stem cells derived from burned skin—a comparative study with umbilical cord stem cells

Abstract: Introduction Burned human skin, which is routinely excised and discarded, contains viable mesenchymal stromal/stem cells (burn-derived mesenchymal stromal/stem cells; BD-MSCs). These cells show promising potential to enable and aid wound regeneration. However, little is known about their cell characteristics and biological function. Objectives This study had two aims: first, to assess critical and cellular characteristics of BD-MSCs and, second, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 64 publications
(41 reference statements)
2
5
0
Order By: Relevance
“…Conditioned medium of hUCMSCs was used to see whether it enhances the migration of broblasts towards the scratch and promotes wound healing. Various studies suggest that the conditioned medium contains growth factors or paracrine mediators which facilitate cells to migrate towards the wound site and help in wound contraction [9,11,28,29]. Our ndings are positively correlated with the reported studies as broblasts treated with conditioned medium have shown signi cantly accelerated cell migration towards the injury site and enhanced wound closure as compared to the untreated broblasts.…”
Section: Analysis Of Wound Tissue By Immunohistochemistrysupporting
confidence: 83%
See 1 more Smart Citation
“…Conditioned medium of hUCMSCs was used to see whether it enhances the migration of broblasts towards the scratch and promotes wound healing. Various studies suggest that the conditioned medium contains growth factors or paracrine mediators which facilitate cells to migrate towards the wound site and help in wound contraction [9,11,28,29]. Our ndings are positively correlated with the reported studies as broblasts treated with conditioned medium have shown signi cantly accelerated cell migration towards the injury site and enhanced wound closure as compared to the untreated broblasts.…”
Section: Analysis Of Wound Tissue By Immunohistochemistrysupporting
confidence: 83%
“…Stem cell therapy has emerged as a promising approach for chronic wounds including cold burns. hUCMSCs can be used in clinical applications for tissue regeneration and cutaneous wound healing [9]. They are known for having the characteristics of self-renewal, multipotent differentiation, and paracrine signaling [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Dolp et al obtained stem cells from discarded burned skin without subcutaneous fat. In comparison with umbilical cord stem cells, there was no significant difference in the expression of MHC I and II, ROS release, or colony formation [ 74 ]. Van der Veen also obtained stem cells from the eschar [ 75 ].…”
Section: Methodsmentioning
confidence: 99%
“…44 BD-MSCs extracted from full thickness burns function like other MSCs and are unaffected by thermal damage in terms of important cell functions involved in burn wound healing. 46…”
Section: Burn Derived Mesenchymal Stem Cells (Bd-msc)mentioning
confidence: 99%